(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Since ancient times, it has been used as a medicine from plants, with a special emphasis on the search for new plants. The ferula plant leaves a impression as an unnecessary, wild plant to a person at first glance. We all met him a lot on the road, in the desert. But we do not all know its healing properties. Tar-juice, which is obtained mainly from glue-Root, is widely used in medicine. The composition of the glue-tar used in medicine is made up of essential oils, organic sulfides that give it the smell of garlic, pinene, coumarins and other compounds. The slime has the properties of a fragile antioxidant, anticholinesterase, anti-inflammatory, anti-tumor.